Petrology and tectonic significance of epidote blueschist-facies rocks from the northern margin of the pelagonian unit in the Republic of North Macedonia - Altherr, Rainer; Hanel, Michael; Soder, Christian; Peters, Daniel; Bahl, Chiara (Journal of petrology, 2023)
In the Republic of North Macedonia, the northern marginal part of the Pelagonian Unit comprises several isolated slivers of low-grade blueschist-facies rocks. These rocks were metamorphosed at conditions of the epidote-blueschist facies with rare transitions to the lawsonite-epidote blueschist facies. If present, lawsonite occurs as relic inclusions in albite, suggesting a local metasomatic enrichment of Na. No aragonite or fibrous calcite was detected, suggesting that the rocks were equilibrated at pressures below the aragonite-calcite boundary. When present, calcite + quartz coexist with glaucophane, epidote, and titanite suggesting the presence of a metamorphic H2O-rich fluid phase with very low XCO2 values (< 0.002). Most samples contain chlorite and only some have garnet, which is nearly free of Mg, but contains an andradite component. Albite only occurs in garnet-free rocks. A core-to-rim decrease of Fe3+/(Fe3++Al3++Cr + Mn3+) in epidote, VIFe3+/VI(Fe3++Al) in blue Na-rich amphibole, and Fe3+/(Fe2++Fe3+) in garnet grains suggest a decrease of ƒO2 during metamorphism. The general absence of magnetite and the presence of very small amounts of hematite in some samples suggest that the hematite-magnetite buffer curve was probably not crossed. It is thought that the investigated blueschist-facies rocks were part of the once highly oxidized sedimentary cover of the subducting oceanic plate. The underlying basaltic crust and oceanic mantle, however, were probably relatively reduced. Aqueous fluids which left this part of the lithosphere during subduction (dehydration) partially reduced the overlying oxidized metasediments. Concerning metamorphic P-T conditions, a pressure range of 0.7-0.9 GPa is defined by the presence of glaucophane + epidote + quartz at the lower boundary and the absence of aragonite at the higher boundary. The temperature range of 320-420°C is defined by the absence of Fe-Mg-pumpellyite at the lower side and the presence of lawsonite + albite at the higher side. These conditions can be narrowed down by using calculated equilibrium mineral assemblage diagrams (pseudosections) for three different bulk-rock compositions, resulting in P = 0.74-0.85 GPa and T = 340-370°C. It must, however, be emphasized that many phases (garnet, glaucophane, epidote, and phengite) show significant chemical zonation, which makes the use of pseudosections problematic.
Gesehen am 19.06.2023